Students' English-Speaking Anxiety At Efl Students Of Papua University - Irma J. E Janis; Yessy A. Winarti (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study focused on students’ English speaking anxiety at EFL students of Papua University. The writer wanted to know the main factor which contributing to first-semester students’ speaking anxiety at the English Education Department of Papua University. It is about anxiety. Speaking anxiety is experienced by students in schools and universities. Speaking anxiety is the problem that the students feel while speaking English. When the students feel anxiety in learning, it can influence the students’ achievement. Almost all of the first-semester students at the English Education Department of Papua University felt speaking anxiety. The present study applied quantitative and qualitative research design. There are 23 students who participated in the study. To collect the data, the writer used two data collection techniques. They are questionnaires and interviews. Based on the result of investigating the dominant factor contributing to the students’ speaking anxiety, the writer found that almost 60% of all students felt fear of making mistakes in speaking English.